What Drives the Participation of Renewable Energy Cooperatives in European Energy Governance? - Tosun, Jale (2019)
What determines the willingness of renewable energy cooperatives (RECs) to strengthen their involvement in politics at the different levels of governments (local/regional, national, transnational)? We address this research question by using data from an original survey distributed to RECs in Germany. The descriptive analysis shows that the RECs are less willing to participate in energy governance at the EU/transnational level than at the national and especially the subnational level. Our analytical findings, first, show that the odds of RECs to participate in governance processes in the future are greater for those RECs that are already involved in such processes. Put differently, we find that engagement in energy governance is affected by path-dependence. Second, participation in subnational governance processes is determined by dissatisfaction with policy decisions taken at that level: the more dissatisfied the respondents, the more likely they are to exert influence in the future. For the Energy Union to realise its aim of incorporating a broader range of stakeholders, the European Commission must highlight the opportunity structure it provides for participating in governance processes.